PENGARUH MODEL PEMBELAJARAN SCRAMBLE TERHADAP HASIL BELAJAR TEMATIK MUATAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN SISWA KELAS III SE-GUGUS 3 SANDEN BANTUL - Handin Handin; Nadziroh Nadziroh (Universitas Sarjanawiyata Tamansiswa, 2020)
This study aims to determine the differences in learning outcomes of PPKn subjects between scramble learning model classes and direct instruction model classes. This type of research is quasi-experiment. The results showed that the learning outcomes of PPKn subjects were taught using a higher scramble learning model while those taught using the direct instruction model were lower. The Z test results obtained Zhitung = 4,2790 and Ztable = 1,645. From the results of the Z test, it can be concluded that Zhitung> Ztable, means that there are differences in learning outcomes of PPKn Subjects between scramble learning model classes and direct instruction model classes. Based on the results of the Z test, it can be concluded that the scramble learning model is more influential than the direct instruction model on the learning outcomes of PPKn Subjects.Â